STRATEGI PENGEMBANGAN DAYA TARIK WISATA PANTAI SERANG, BLITAR SEBAGAI LOKASI AKTIVITAS FAMILY LEISURE AND RECREATION - Aisy, Nurul; Oka Karini, Ni Made; Sudana, I Putu (Jurnal IPTA (Industri Perjalanan Wisata); Vol 11 No 1 (2023): Jurnal IPTA (July 2023)DO - 10.24843/IPTA.2023.v11.i01.p14, 2023)
The survey aims to knowing the appropriate strategy in developing the tourist attraction of Serang Beach as a location for family leisure and recreation in Blitar Regency.Dalam this researchusing mix methods, namely descriptive qualitative and quantitative. Data was collected by means of observation, interviews, and documentation. The next step is to analyze the internal environment of Serang Beach tourist attraction, which is analyzed based on tourism potential 4A, while the external environment is based on PEST. Then analyze the internal environment and external environment using IFAS and EFAS matrices. The internal environment gets a total score of 3.13 which is greater than the total score of external factors, which is 0.03. So based on these results, the tourist attraction of Serang Beach as a location for family leisure and recreation activities is included in quadrant I, which means the appropriate strategy is grow and build. Next, formulate a development strategy using the SWOT matrix to produce SO, WO, ST, and SO strategies. and WT. based on the results of the IFAS and EFAS weighting scores, in the internal environment the highest total score is on strengths, while external factors are on opportunities, so the strategy that can be applied in the short term is SO.